Bridging Small-Gap Peripheral Nerve Defect Using Silicone Rubber Chamber in the Rat Sciatic Nerve Transection Model - Roza Fallah; Keyvan Amini; Rahim Mohammadi; Saeed Azizi; Kiana Karegar (Veterinary Research Forum, 2010)
Despite promising results observed using silicone rubber chamber, no previous comprehensive work was performed on behavior of the conduit. Present study aimed at further functional, histomorphometrical and immunohistochemical assessment of nerve regeneration in the same animal along a 10-mm rat sciatic nerve gap. Fifty- four male Wistar rats were divided into three experimental groups (n = 18), randomly: Sham-operation (NC), Transected control (TC) and silicone conduit (SIL). In NC group after anesthesia left sciatic nerve was exposed through a gluteal muscle incision and after haemoestasis the muscle was sutured. In TC group left sciatic nerve was exposed the same way and transected proximal to the tibio-peroneal bifurcation leaving a 10-mm gap. In SIL group left sciatic nerve was transected the same way and proximal and distal stumps were each inserted into a silicone tube. Each group was subdivided into three subgroups of six animals each and were studied 4, 8, 12 weeks after surgery. Functional analysis showed significant improvement of nerve function in SIL group than in TC group (P < 0.05). Morphometric indices and immuohistochemistry indicated there were significant differences (P < 0.05) between SIL and TC groups 12 weeks after surgery. Silicone entubulation technique has offered the hope of providing a method for achieving the peripheral nerve regeneration in the least harmful way that is available, easily performed. Using silicone tubes in bridging of nerve defects could be promising because it is inert and does not induce extensive scarring or degeneration after implantation.